Financial Risk, Corporate Governance, And Financial Performance: An Empirical Study On Bank Indonesia - Marselino Wau; Jhon Firman Fau; Kristiurman Jaya Mendrofa; Zaitul (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study explores the interplay of financial risk and corporate governance on Bank Indonesia's performance. Data from 19 Exchange-listed Indonesian banks' 2020-2022 reports were analyzed via variable and PLS-SEM methods. Credit risk impact was found minor, while market risk significantly influenced performance. Managerial ownership positively affected, while public ownership had substantial impact. Thus, governance disclosure affects bank performance. Managing market risks and enhancing ownership practices is crucial. Findings suggest revising credit risk assessment for indirect performance betterment. Improving governance and addressing market risk can elevate banking performance. Insights guide the sector in enhancing performance determinants, informed by this study. Keywords: Financial Risk, Corporate Governance, and Financial Performance.